Pelatihan Penggunaan Mendeley sebagai Upaya Meningkatkan Kompetensi Manajemen Referensi Ilmiah bagi Mahasiswa - Raihani Raihani; Nurrahmah Nurrahmah; Ruaida Ruaida; Yusri Yusuf; Rostina Taib; Al Furqan (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
The ability to manage scientific references is an essential competency that university students must possess in preparing academic papers. However, many students still encounter difficulties in citing sources and compiling bibliographies systematically, which may lead to writing errors and violations of academic integrity. This community service program aimed to improve students' competencies in scientific reference management through training on the use of the Mendeley application. The training was conducted using lectures, demonstrations, hands-on practice, and mentoring. The program was evaluated through pre-tests, post-tests, observations during the practical sessions, and participant satisfaction questionnaires. The results showed that the training successfully improved participants' competencies across all assessed indicators, including understanding the functions of Mendeley, installing the application, managing references, generating automatic citations, and creating bibliographies. The participants' average competency score increased from 28.3% in the pre-test to 96.7% in the post-test. Furthermore, the participant satisfaction evaluation yielded an average score of 87.2%, categorized as very good, indicating positive responses toward the training materials, instructional methods, and mentoring provided. Therefore, the Mendeley training proved effective in enhancing students' scientific reference management competencies and supporting the preparation of academic papers that are more systematic, efficient, and compliant with academic writing standards.